Learning and using languages in ethnographic research - Tremlett, Annabel; Danero Iglesias, Julien; Gibb, Robert, 1969- (Researching multilingually, 2019)
"This book breaks the silence that surrounds learning a language for ethnographic research and in the process demystifies some of the multilingual aspects of contemporary ethnographic work. It offers a set of engaging and accessible accounts of language learning and use written by ethnographers who are at different stages of their academic career"--